Jane Eyre : Usborne English Readers Level 3 - Brontë, Charlotte (Editorial Usborne, 2020)
Jane Eyre is an orphan, poor and ordinary-looking. Her life is poor and ordinary too until she comes to Thornfield Hall and meets Mr. Rochester; but Thornfield hides a dangerous secret. Includes a word list, 5 pages of activities and free online audio (British English and American English).